NEGATIVE SELECTION BASED FUZZY FAULT DIAGNOSIS MODEL - Aydin, Ilhan; Karakose, Mehmet; Akin, Erhan (Gazi Univ, Fac Engineering Architecture, 2009)
Fault diagnosis is important to ensure the continuity in the systems that the studies in this area have increased. The effectiveness of fault diagnosis methods has been enhanced by using intelligent computing techniques. In this study, a fault diagnosis method based on fuzzy logic and negative selection is proposed. In the proposed algorithm, the broken rotor bar related features are extracted using negative selection algorithm that is a component of the artificial immune system. In addition, the direction of spectrum changing obtained using the motor current signature analysis is given to fuzzy logic system and the faults are diagnosed. A new weighted affinity measurement is presented for negative selection. The broken rotor bar faults, stator and bearing friction faults occurred in induction motors can be diagnosed by using proposed method. The output of the method gives both the fault type and the severity of fault to determine the multiple faults. The performance of proposed method is verified using healthy and faulty motor data that are obtained as simulation and experimentally.
Keywords: Artificial immune systems; negative selection algorithm; fuzzy logic; induction motor; fault diagnosis